2020
DOI: 10.1155/2020/9607328
|View full text |Cite
|
Sign up to set email alerts
|

Prevotella Induces the Production of Th17 Cells in the Colon of Mice

Abstract: Th17-mediated mucosal inflammation is related to increased Prevotella bacterial abundance. The actual involvement of Prevotella in the development and accumulation of intestinal Th17 cells at a steady state, however, remains undefined. Herein, we investigated the role of Prevotella in inducing intestinal Th17 cells in mice. Mice were treated with a combination of broad-spectrum antibiotics (including ampicillin, neomycin sulfate, vancomycin hydrochloride, and metronidazole) in their drinking water for 4 weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 56 publications
2
28
0
Order By: Relevance
“…Proteobacteria and Actinobacteria are associated with infiltrating immune cells in lung tissue, including neutrophils, eosinophils, and B cells (Sze et al, 2015). Moreover, increased Prevotella abundance was associated with augmented T-helper type 17 (Th17)-mediated mucosal inflammation, which was in line with the marked capacity of Prevotella in driving Th17 immune responses in vitro (Huang et al, 2020). Neisseria, such as Neisseria meningitidis, is a colonizing bacterium in the respiratory tract, which can cause diseases under certain conditions.…”
Section: Discussionmentioning
confidence: 85%
“…Proteobacteria and Actinobacteria are associated with infiltrating immune cells in lung tissue, including neutrophils, eosinophils, and B cells (Sze et al, 2015). Moreover, increased Prevotella abundance was associated with augmented T-helper type 17 (Th17)-mediated mucosal inflammation, which was in line with the marked capacity of Prevotella in driving Th17 immune responses in vitro (Huang et al, 2020). Neisseria, such as Neisseria meningitidis, is a colonizing bacterium in the respiratory tract, which can cause diseases under certain conditions.…”
Section: Discussionmentioning
confidence: 85%
“…make a considerable contribution to the carbohydrates and nitrogen utilization of ruminants [ 47 , 48 ]. Previous research also indicated favorable influences of some Prevotella strains on the improvement of immunity [ 49 ]. Therefore, Prevotella is conducive to the health and growth of dairy cows, which in turn contributes to the improvement of milk production and quality.…”
Section: Discussionmentioning
confidence: 97%
“…CRP, as a nonspecific marker of inflammation and tissue damage, its increased levels suggest an increased pro-inflammatory response. However, the gram-negative bacteria Prevotella can induce the transformation of Type 1 T helper cells (Th1) to Type 2 T helper cells (Th2) through lipopolysaccharide (LPS) on their outer membrane to activate the intestinal immune inflammatory system and then destroy the intestinal barrier to cause a “leaky gut” ( 34 , 35 ), triggering a congenital autoimmune response against thyroid cells ( 36 ), which may lead to a reduction in serum thyroid hormone levels and increase TSH levels by negative feedback mechanisms, thereby leading to hypothyroidism. Moreover, we found a significant positive correlation between serum FT4 level and the abundance of Blautia .…”
Section: Discussionmentioning
confidence: 99%